Peptide Design for Enhanced Anti-Melanogenesis: Optimizing Molecular Weight, Polarity, and Cyclization - Putri SA; Maharani R; Maksum IP; Siahaan TJ (Drug Design, Development and Therapy)
Selvi Apriliana Putri,1 Rani Maharani,1 Iman Permana Maksum,1 Teruna J Siahaan2 1Department of Chemistry, Faculty of Mathematics and Natural Sciences, Padjadjaran University, Bandung, 40173, Indonesia; 2Department of Pharmaceutical Chemistry, School of Pharmacy, The University of Kansas, Lawrence, KS, 66047, USACorrespondence: Iman Permana Maksum, Department of Chemistry, Faculty of Mathematics and Natural Sciences, Padjadjaran University, Bandung, 40173, Indonesia, Email iman.permana@unpad.ac.idAbstract: Melanogenesis is a biochemical process that regulates skin pigmentation, which is crucial role in protecting against ultraviolet radiation. It is also associated with hyperpigmentation conditions such as melasma and age spots, which negatively impact aesthetics and self-confidence. Tyrosinase (TYR), a key enzyme in the melanogenesis pathway, catalyzes the biosynthesis of melanin in the skin. Inhibition of tyrosinase particularly by blocking its active site and preventing the binding of natural substrates such as tyrosine, can reduce melanin production, making it a promising therapeutic target for treating hyperpigmentation. Peptides have emerged as promising therapeutics to regulate melanogenesis by minimizing the side effects associated with conventional skin whitening therapeutics. This review is designed to offer a comprehensive analysis of current strategies in peptide design aimed at optimizing anti-melanogenic activity, by focusing on the role of molecular weight, polarity, and cyclization strategies in enhancing peptide efficacy and stability. It was found that optimal peptide size was within the range of 400– 600 Da. The balance between hydrophilic and hydrophobic properties in peptides is crucial for effective TYR inhibition, as higher hydrophilicity enhances affinity for the TYR active site and stronger catalytic inhibition, while hydrophobicity can contribute through alternative mechanisms. Cyclization of peptides enhances their structural stability, serum resistance, and binding affinity while reducing toxicity. This process increases resistance to enzymatic degradation and improves target specificity by limiting conformational flexibility. Additionally, the rigidity and internal hydrogen bonding of cyclic peptides can aid in membrane permeability, making them more effective for therapeutic use. Peptide optimizations through size modification, polarity change, and cyclization strategies have been shown to be promising as reliable and safe agents for melanin inhibition. Future studies exploring specific amino acid in peptide chains are required to improve efficacy and potential clinical applications of these anti-melanogenic peptides as a hyperpigmentation treatment. Keywords: anti-hyperpigmentation, anti-melanogenesis, amino acid, tyrosinase, TYR